2011
DOI: 10.1371/journal.pone.0023274
|View full text |Cite
|
Sign up to set email alerts
|

hSulf-1 Gene Exhibits Anticancer Efficacy through Negatively Regulating VEGFR-2 Signaling in Human Cancers

Abstract: BackgroundHuman sulfatase 1 (hSulf-1) is a heparin-degrading endosulfatase that desulfates cell surface heparan sulfate proteoglycans (HSPGs) in extracellular matrix and negatively modulates heparin-binding growth factor and cytokine signaling in cell proliferation. But hSulf-1 function is more complicated, and its molecular mechanism has not been well known.Principal FindingsTo further investigate the functions of hSulf-1 gene in regulating the vascular endothelial growth factor receptor (VEGFR) signaling, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Our finding that SDC1 over-expression directly inhibits SULF1 and leads to increased HS 6-O-sulfation suggests functional consequences regarding the binding of growth factors and the regulation of intracellular signaling pathways, as previously observed for VEGFR [60], amphiregulin [61], and FGFR [62]. In our study, this is illustrated by a subtle enhancement of EGFR activity in cells over-expressing SDC1 and concomitant activation of the downstream ERK1/2 pathway.…”
Section: Discussionsupporting
confidence: 87%
“…Our finding that SDC1 over-expression directly inhibits SULF1 and leads to increased HS 6-O-sulfation suggests functional consequences regarding the binding of growth factors and the regulation of intracellular signaling pathways, as previously observed for VEGFR [60], amphiregulin [61], and FGFR [62]. In our study, this is illustrated by a subtle enhancement of EGFR activity in cells over-expressing SDC1 and concomitant activation of the downstream ERK1/2 pathway.…”
Section: Discussionsupporting
confidence: 87%
“…Such targets would have the potential for the creation of high-performance targeted agents for HCC therapy. Many studies have shown that significant amounts of the ligands for multiple signaling pathways can be sequestered by binding to HSPGs on the cell surface and in the extracellular matrix (Sanderson et al, 2005; Selleck, 2006; Ji et al, 2011). SULF2 is a novel member of a family of HS-degrading endosulfatases that can desulfate HS, releasing ligands bound to HSPGs and consequently modulating multiple signaling pathways (Rosen and Lemjabbar-Alaoui, 2010; Bret et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that HSULF-1’s hydrolysis of sulfate groups from HSPGs down-regulates the receptor tyrosine kinase activity to attenuate cell growth and survival through signaling pathways regulated by FGF-2, VEGF, and HGF [19,30,31]. Based on these findings, H292 cells were forced to over-express HSULF-1 and levels of p-ERK and p-Akt, common down-stream targets of signaling pathways triggered by FGF-2, VEGF, and HGF, were analyzed.…”
Section: Discussionmentioning
confidence: 99%